Peran Kepemimpinan Transformasional, Kompetensi, Kesiapan Berubah dalam Mencapai Kinerja pada masa Pandemi: (The Role of Transformational Leadership, Competence, Readiness to Change in Achieving Performance during a Pandemic) - Siti Nur Khotijah; Sigit Wibowo Dwi Nugroho; Dwita Darmawati (e-Journal Ekonomi Bisnis dan Akuntansi, 2022)
This study aims to analyze the effect of transformational leadership and competence on employee performance during the Covid-19 pandemic, either directly or through mediation of readiness to change. By using purposive sampling method, 76 respondents were selected from 93 employees of CV Anggraini Sejati Cemerlang. The results of the analysis using SEM PLS show that (1) Transformational leadership has a positive effect on employee performance, (2) Competence has a positive effect on employee performance, (3) Readiness to change does not mediate the influence of both transformational leadership and competence on employee performance. Based on the results of this research, it is expected that leaders will continue to adopt and improve the transformational leadership style and continue to provide encouragement so that employees can excel, provide training, provide opportunities for employees to solve problems in their own way and appreciate employee contributions. management needs to improve the competence of their employees by continuing to provide job training, so that they understand more about their work and employees can have bright ideas to advance the company.